Dose- and time-dependent antiplatelet effects of aspirin - Perneby, Christina; Wallén, N. Håkan; Rooney, Cathy; Fitzgerald, Desmond; Hjemdahl, Paul (Thrombosis and Haemostasis, 2006)
Aspirin is widely used, but dosages in different clinical situations and the possible importance of “aspirin resistance” are debated. We performed an open cross-over study comparing no treatment (baseline) with three aspirin dosage regimens – 37.5 mg/ day for 10 days, 320 mg/day for 7 days, and, finally, a single 640 mg dose (cumulative dose 960 mg) – in 15 healthy male volunteers. Platelet aggregability was assessed in whole blood (WB) and platelet rich plasma (PRP).The urinary excretions of stable thromboxane (TxM) and prostacyclin (PGI-M) metabolites, and bleeding time were also measured. Platelet COX inhibition was nearly complete already at 37.5 mg aspirin daily, as evidenced by >98 % suppression of serum thromboxane B2 and almost abolished arachidonic acid (AA) induced aggregation in PRP 2–6 h after dosing. Bleeding time was similarly prolonged by all dosages of as- pirin. Once daily dosing was associated with considerable recovery of AA induced platelet aggregation inWB after 24 hours, even after 960 mg aspirin. Collagen induced aggregation in WB with normal extracellular calcium levels (hirudin anticoagulated) was inhibited <40% at all dosages. TxM excretion was incompletely suppressed, and increased <24 hours after the cumulative 960 mg dose. Aspirin treatment reduced PGI-M already at the lowest dosage (by ≈25%), but PGI-M excretion and platelet aggregability were not correlated. Antiplatelet effects of aspirin are limited in WB with normal calcium levels. Since recovery of COX-dependent platelet aggregation occurred within 24 hours, once daily dosing of aspirin might be insufficient in patients with increased platelet turnover.
Keywords: Platelet function; thromboxane; prostacyclin; acetylsalicylic acid; dosage